Effectiveness of Family Integrated Care in neonatal intensive care units on infant and parent outcomes: a multicentre, multinational, cluster-randomised controlled trial. (April 2018) - O'Brien, Karel; Robson, Kate; Bracht, Marianne; Cruz, Melinda; Lui, Kei; Alvaro, Ruben; da Silva, Orlando; Monterrosa, Luis; Narvey, Michael; Ng, Eugene; Soraisham, Amuchou; Ye, Xiang Y; et al.
Summary: Background: Despite evidence suggesting that parent involvement was beneficial for infant and parent outcomes, the Family Integrated Care (FICare) programme was one of the first pragmatic approaches to enable parents to become primary caregivers in the neonatal intensive care unit (NICU). We aimed to analyse the effect of FICare on infant and parent outcomes, safety, and resource use. Methods: In this multicentre, cluster-randomised controlled trial, we stratified 26 tertiary NICUs from Canada, Australia, and New Zealand by country and size, and assigned them, using a computer-generated random allocation sequence, to provide FICare or standard NICU care. Eligible infants were born at 33 weeks' gestation or earlier, and had no or low-level respiratory support; parents gave written informed consent for enrolment. To be eligible, parents in the FICare group had to commit to be present for at least 6 h a day, attend educational sessions, and actively care for their infant. The primary outcome, analysed at the individual level, was infant weight gain at day 21 after enrolment. Secondary outcomes were weight gain velocity, high frequency breastfeeding (≥6 times a day) at hospital discharge, parental stress and anxiety at enrolment and day 21, NICU mortality and major neonatal morbidities, safety, and resource use (including duration of oxygen therapy and hospital stay). This trial is registered withClinicalTrials.gov, numberNCT01852695 . Findings: From Oct 1, 2012, 26 sites were randomly assigned to provide FICare (n=14) or standard care (n=12). One site assigned to FICare discontinued because of poor site enrolment. Parents and infants were enrolled between April 1, 2013, and Aug 31, 2015, with 895 infants being eligible in the FICare group and 891 in the standard care group. At day 21, weight gain was greater in the FICare group than in the standard care group (mean change in Z scores –0·071 [SD 0·42] vs –0·155 [0·42]; p<0·0002). Average daily weight gain was significantly higher in infants receiving FICare than those receiving standard care (mean daily weight gain 26·7 g [SD 9·4] vs 24·8 g [9·5]; p<0·0001). The high-frequency exclusive breastmilk feeding rate at discharge was higher for infants in the FICare group (279 [70%] of 396) than those in the standard care group (394 [63%] of 624; p=0·016). At day 21, parents in the FICare group had lower mean stress scores than did parents in the standard care group (2·3 [SD 0·8] vs 2·5 [0·8]; p<0·00043), and lower mean anxiety scores (70·8 [20·1] vs 74·2 [19·9]; p=0·0045). There were no significant differences between groups in the rates of the secondary outcomes of mortality, major morbidity, duration of oxygen therapy, and duration of hospital stay. Although the safety assessment was not completed, there were no adverse events. Interpretation: FICare improved infant weight gain, decreased parent stress and anxiety, and increased high-frequency exclusive breastmilk feeding at discharge, which together suggest that FICare is an important advancement in neonatal care. Further research is required to examine if these results translate into better long-term outcomes for families. Funding: Canadian Institutes of Health Research Partnerships for Health System Improvement, and Ontario Ministry of Health and Long-Term Care.